EDUKASI PEMBUATAN DAN DISTRIBUSI HANDSANITIZER DARI DAUN SIRIH KEPADA MASYARAKAT DI DESA HAULASI KECAMATAN MIOMAFFO BARAT - Lukas Pardosi; Desta Gloria Siahaan (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2023)
This activity was an education for making and distribution of handsanitizer made from natural ingredients, namely green betel leaf (Piper betle, L.), aloe vera (Aloe vera), lime (Citrus aurantifolia) and perfume to add fragrance to the handsanitizer . This activity was carried out for one day in Haulasi Village, West Miomaffo District, North Central Timor Regency, East Nusa Tenggara Province. Education on how to make and distribute handsanitizer s is carried out by visiting residents' houses door-to-door. The results of this activity were; 1) The community in Haulasi Village, West Miomaffo District, obtained information on how to make their own handsanitizer from natural ingredients. 2) People in Haulasi Village, West Miomaffo District knew how to use handsanitizer and the benefits of handsanitizer . 3) The handsanitizer can be used by the community to maintain hand hygiene to avoid the Covid-19 virus.